Expression of miRNA-29c in the carotid plaque and its association with diabetic mellitus - Wang, Hua; Mai, Peipei; He, Fang; Zhang, Yanfang (Frontiers in Cardiovascular Medicine, 2024)
Background: Carotid artery atherosclerosis is a major cause of ischemic stroke, and ischemic stroke is the leading cause of morbidity and mortality worldwide.Unfortunately, the reason for the build-up of atherosclerosis plaque is unknown. The miRNA-29c was reported to promote the phenotype transformation of vascular smooth muscle cells (VSMCs) in diabetes mice, eventually leading to plaque formation and bleeding. However, such studies are rare and limited to animal experiments.Methods: In our study, 40 patients were divided into a diabetic mellitus (DM) group and a non-DM group according to whether they were diagnosed with DM. Then, the real-time quantitative PCR was applied to examine the miRNA-29c level in human carotid plaque tissue derived from 40 subjects receiving carotid endarterectomy.Results: Briefly, diabetes patients had a decreased miRNA-29c level as compared with non-DM subjects, and this comparison was statistically significant (P = 0.02).Notably, variable miRNA-29c level was negatively associated with HbA1c level, although no statistical significance was observed. Moreover, there was an increased miRNA-29c level in patients with cerebral stroke.Collectively, the miRNA-29c level in the carotid plaque is closely associated with DM and cerebral stroke, which may contribute to atherosclerosis formation.